Lactogenesis in the rat. Metabolism of uridine diphosphate galactose by mammary gland - Kuhn, N. J. (1968)
1. Lactose synthetase activity in the rat mammary gland increases during the last day of pregnancy from an essentially zero value. There is a parallel increase of tissue lactose and of glucose 6-phosphate dehydrogenase activity. 2. Mammary-gland homogenates prepared both before and after parturition hydrolyse the lactose precursors glucose 6-phosphate, glucose 1-phosphate, UDP-glucose, UDP-galactose and also maltose, but not lactose. 3. A role of lactose synthetase as the rate-limiting enzyme for lactose biosynthesis and the possible significance of the hydrolytic activities are discussed with respect to lactogenesis.